Estudos in silico para identificação de alvos moleculares para quinolinas com potencial atividade antileishmaniose - Silva, Marília Cecília da (2024)
Leishmaniasis is a neglected tropical disease, the most severe form of which is visceral. Quinoline derivatives have shown therapeutic potential in a number of diseases, including leishmaniasis, especially caused by the species Leishmania donovani and Leishmania infantum. Identifying the mechanism of action for these compounds is of fundamental interest in rational drug design, which includes computational studies based on the structure of biological receptors. Computational simulations have been widely used to identify molecular targets, given the high cost of conventional methods used for this purpose. In this context, the aim of this study was to identify the probable mechanism of action of quinoline derivatives, with a focus on L. donovani, and to evaluate the molecular interactions present in the formation of the complex by means of the computational simulations. Target Fishing approach was used in this study to identify a potential biological target for a set of quinoline derivatives with potential leishmanicidal activity. Based on the three-dimensional structures of the molecular targets obtained by inverse docking, pharmacophore models were built in order to investigate the main areas of ligand-receptor interaction using the GOLD programme. The models that best described the modes of interaction with the most promising compound determined by the docking studies were used as a starting structure for Molecular Dynamics (MD) simulations. Part of the targets with the best docking scores were specific to L. major, with the N-myristoyltransferase (NMT) enzyme standing out as the main target for this species. Model based on the PDB 2WSA code structure provided the best results in statistical terms. DM simulations demonstrated that the most promising ligand presented an RMSD of under 2 Å, which demonstrates the good stability of the complex formed. This compound exhibited a promising pharmacodynamic profile, with high affinity for both enzymes, which suggests that compound 1G is a promising NMT inhibitor. The results indicate that interaction with LdNMT may be a relevant mechanism of action for the set of quinolines investigated.